Wearable Sensors in Sport A Practical Guide to Usage and Implementation - Lee, James; Wheeler, Keane; James, Daniel A. (SpringerBriefs in Applied Sciences and Technology,, 2019)
Drawing on 15 years of experience in the development and use of wearable sensors in sports science, this book bridges the gap between technical research and the widespread adoption of inertial sensors in biomechanical assessment and ambulatory studies of locomotion. It offers a 'no-nonsense' guide to using inertial sensors for readers from the sports science disciplines who may be unfamiliar with the terms, concepts and approaches that lead to these sensors' successful use. At the same time, the book introduces readers with a technical background, e.g. in engineering, to sport science methodologies that can provide valuable insights into the use of sensors in a practical environment that extends well beyond bench testing. .